2007
DOI: 10.1111/j.1600-0897.2007.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of the Rat Endometriosis Model

Abstract: The results suggest that osteopontin, Lyn, Vav1, Runx1, and l-selectin play important roles in the pathogenesis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 53 publications
3
29
0
1
Order By: Relevance
“…2) showed expression of LCN2 in mammalian uterine tissue during endometriosis formation. Our findings are consistent with a previous report that showed LCN2 upregulation in a rat model of endometriosis (Konno et al 2007).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…2) showed expression of LCN2 in mammalian uterine tissue during endometriosis formation. Our findings are consistent with a previous report that showed LCN2 upregulation in a rat model of endometriosis (Konno et al 2007).…”
Section: Discussionsupporting
confidence: 83%
“…As mentioned earlier, LCN2 is upregulated in the endometriotic lesions (Konno et al 2007, Becker et al 2010. We previously found that LCN2 is upregulated in the endometrial carcinoma cells (RL95-2 cells derived from endometrial epithelia) under oxidative stress and that LCN2-induced secreted cytokines trigger cell proliferation and migration (Lin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Global gene expression studies in both human and animal models have shown that endometriotic lesions have aberrant gene expression profiles when compared to normal endometrium. [3][4][5][6][7] The mechanisms at play have not been sufficiently studied, but epigenetic regulation of gene expression is emerging as a key player in endometriosis. 8 Thus, the current knowledge on the pathophysiology of endometriosis supports the involvement of both genetic and epigenetic phenomena in inducing changes in gene expression that lead to disease.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, which do not experience menses, endometriosis with proliferating stromal lesions do not occur spontaneously but can be induced by autotransplantation of endometrium (Uchiide et al, 2002). In the endometriosis model induced by autotransplantation of endometrium, enhanced inflammatory reactions and expression of cytokines and chemokines has been reported (Flores et al, 2007;Konno et al, 2007;Umezawa et al, 2008b). Endometriosis in this model is induced within four days post-autotransplantation, peaking at seven days, and declining within 14 days post-surgery (Uchiide et al, 2002).…”
Section: Discussionmentioning
confidence: 95%